2014
DOI: 10.1111/jdv.12773
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of open‐label ixekizumab treatment in Japanese patients with moderate‐to‐severe plaque psoriasis, erythrodermic psoriasis and generalized pustular psoriasis

Abstract: By Week 12, nearly all patients with PP, EP and GPP achieved PASI75. The safety profile was consistent with reported results and no unexpected safety signals were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
154
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(169 citation statements)
references
References 14 publications
13
154
0
2
Order By: Relevance
“…This is consistent with recently published case series showing six out of eight erythrodermic patients achieving complete clearance with anti-IL-17 treatment (Saeki et al , 2015), but similar data on flexural psoriasis does not yet exist. In addition, our data demonstrates pronounced differences in the expression of several key pro-inflammatory cytokines between each clinical subtype, suggesting that while IL-17 may provide a common inflammatory pathway, other inflammatory signals may modify the clinical presentation and contribute to unique manifestations of each subtype.…”
supporting
confidence: 92%
“…This is consistent with recently published case series showing six out of eight erythrodermic patients achieving complete clearance with anti-IL-17 treatment (Saeki et al , 2015), but similar data on flexural psoriasis does not yet exist. In addition, our data demonstrates pronounced differences in the expression of several key pro-inflammatory cytokines between each clinical subtype, suggesting that while IL-17 may provide a common inflammatory pathway, other inflammatory signals may modify the clinical presentation and contribute to unique manifestations of each subtype.…”
supporting
confidence: 92%
“…IL17 inhibitors including secukinumab [54] and ixekizumab [55,56], and the IL17 receptor [62]. Therefore, drugs that target IL17 and its receptor are an important part of the future armament against PsA.…”
Section: Il17 Blockadementioning
confidence: 99%
“…No cases of neutropenia (<1000-1500 cells/ml) were reported during the 52-week open-label extension study. In the Phase III study by Saeki et al, a decrease in mean neutrophil count was found in 18.7% of patients (-2.2 ± 1.6 billion/l), grade 1 neutropenia was found in 15 patients and grade 2 neutropenia in 4 patients [37]. Neutropenia as an adverse effect is not only observed in ixekizumab trials but also in trials with brodalumab and secukinumab.…”
Section: Safetymentioning
confidence: 89%
“…This is a Phase III, open-label study that included [37]. Although based on a small sample size, all patients with erythrodermic psoriasis treated with ixekizumab reached PASI 75 at week 12 and maintained the effect throughout the 24-week study.…”
Section: Phase III Trialsmentioning
confidence: 99%